Production potential and economics of different rice (Oryza sativa)-based cropping systems in Andhra Pradesh - Krishana, A; Reddy, K Anand (The Indian Journal of Agricultural Sciences, 2013)
A 3-year (1989-92) experiment conducted at Rudrur: with 6 rice (Oryza sativa L.)-based crop sequences, viz rice with safflower (Carthannus tinctorius L.), indian mustard [Brassica juncea (L.) Czernj, & Cosson], bengal gram (Cicer arietinum L.), maize (Zea mays L.), wheat (Triticum aestivum L. emend. Fiori & Paol.) and sunflower (Helianthus annuus L.) showed that rice-sunflower gives significantly higher rice equivalent yield (8.48 tonnes/ha), higher production efficiency (36.4 kg/ha/day), higher net return Rs 26 160/ha) and benefit : cost ratio (3.18). This was followed by rice-bengal gram with rice-equivalent yield, 7.97 tonnes/ha, net return Rs 23 865/ha and benefit : cost ratio 2.98. The land-use efficiency of rice with bengal gram, indian mustard, wheat or sunflower was 61-64% in the year, whereas that of rice with safflower or maize was 65-71 %. The value of sustainable yield index revealed that rice-sunflower system was more stable (89%), followed by rice-bengal gram (82.8%).